Platelet-activating factor acetylhydrolase and transacetylase activities in human aorta and mammary artery* - Demokritos C. Tsoukatos; Isabelle Brochériou; Vassilios Moussis; Christina P. Panopoulou; Elena D. Christofidou; Stamatis Koussissis; Socratis Sismanidis; Ewa Ninio; Stavros Siminelakis (Journal of Lipid Research, 2008)
Platelet-activating factor (PAF), the potent phospholipid mediator of inflammation, is involved in atherosclerosis. Platelet-activating factor-acetylhydrolase (PAF-AH), the enzyme that inactivates PAF bioactivity, possesses both acetylhydrolase and transacetylase activities. In the present study, we measured acetylhydrolase and transacetylase activities in human atherogenic aorta and nonatherogenic mammary arteries. Immunohistochemistry analysis showed PAF-AH expression in the intima and the media of the aorta and in the media of mammary arteries. Acetylhydrolase and transacetylase activities were (mean ± SE, n = 38): acetylhydrolase of aorta, 2.8 ± 0.5 pmol/min/mg of tissue; transacetylase of aorta, 3.3 ± 0.7 pmol/min/mg of tissue; acetylhydrolase of mammary artery, 1.4 ± 0.3 pmol/min/mg of tissue (P < 0.004 as compared with acetylhydrolase of aorta); transacetylase of mammary artery, 0.8 ± 0.2 pmol/min/mg of tissue (P < 0.03 as compared with acetylhydrolase of mammary artery). Lyso-PAF accumulation and an increase in PAF bioactivity were observed in the aorta of some patients. Reverse-phase HPLC and electrospray ionization mass spectrometry analysis revealed that 1-O-hexadecyl-2 acetyl-sn glycero-3-phosphocholine accounted for 60% of the PAF bioactivity and 1-O-hexadecyl-2-butanoyl-sn-glycerol-3-phosphocholine for 40% of the PAF bioactivity. The nonatherogenic properties of mammary arteries may in part be due to low PAF formation regulated by PAF-AH activity. In atherogenic aortas, an imbalance between PAF-AH and transacetylase activity, as well as lyso-PAF accumulation, may lead to unregulated PAF formation and to progression of atherosclerosis.